Efeito inibitório de estatinas in vitro sobre células planctônicas e biofilmes de espécies do complexo Sporothrix schenckii - Fonseca, Xhaulla Maria Quariguasi Cunha (2020)
Sporotrichosis is a subcutaneous disease caused by dimorphic fungi belonging to the Sporothrix schenckii species complex, which antifungal drugs such as amphotericin B, itraconazole and terbinafine are used for treatment, however the toxicity and emergence of strains with low susceptibility to these drugs have stimulated the expansion of the sporotrichosis therapeutic arsenal. In this context, the statins are cholesterol-lowering drugs that have potential antimicrobial activity. Regardin the high cost of developing drugs, their repositioning has been an alternative and it is a strategy applicable to the expansion of the sporotrichosis therapeutic arsenal. Therefore, the antifungal activity of simvastatin, atorvastatin and pravastatin on planktonic cells and biofilms of Sporothrix schenckii species complex was evaluated. In addition, the interaction of pravastatin with amphotericin B, itraconazole and terbinafine was also evaluated. Eighteen strains of Sporothrix spp. (08 S. brasiliensis, 04 S. globosa, 02 S.mexicana and 04 S. schenckii stricto sensu) were used in this study. Therefore, the planktonic susceptibility of the filamentous and leveruriform forms of Sporothrix spp. was evaluated by broth microdilution method. The biofilms formed from the filamentous forms of these fungi were exposed to statins and their metabolic activity measured by XTT reduction colorimetric assay. Thus, the minimum inhibitory concentrations (MICs) of statins ranged from 8 to 512 μg.ml-1 for filamentous forms and from 8 to 256 μg.ml-1 for yeast forms, respectively. MICs capable of inhibiting 50% and 90% (BCIM50 and BMIC90) of statin-exposed biofilm growth were 128 < BCIM50 > 2048 μg.ml-1 and 512 < BMIC90 > 2048 μg.ml-1, respectively; 128 < BCIM50 > 512 μg.ml-1 and BMIC90 > 2048 μg.ml-1 for atorvastatin, respectively; and BCIM50 > 2048 μg.ml-1 and BMIC90 > 2048 μg.ml-1 for pravastatin. In addition, pravastatin showed indifferent interactions with amphotericin B, itraconazole or terbinafine. Finally, simvastatin, atorvastatin and pravastatin showed antifungal activity on planktonic cells of Sporothrix spp. in filamentous and yeast forms. In addition, simvastatin and atorvastatin inhibited biofilms of the filamentous form of Sporothrix spp. These results highlight the antifungal and antibiofilm potential of statins, in particular simvastatin and atorvastatin.